REFLECTING ON THE ACHIEVEMENTS OF AGRARIAN REFORM AND ITS IMPACT ON THE ECONOMIC SYSTEM TOWARDS GOLDEN INDONESIA 2045: WEST JAVA CASES - Darmawan, Dalu; Soetarto, Endriatmo; Asnawi, Yudha Heryawan; Sukmawati, Anggraini; Mahasari, Jamaluddin (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
Land use and land tenure implemented through agrarian reform in the concept of the Land management paradigm are reflected in praxis that improves people's welfare. The welfare of the people achieved is in line with realizing the vision of Golden Indonesia 2045. The current problematic situation is an argumentative discussion on assessing the success of agrarian reform that improves people's welfare towards the Golden Indonesia 2045. This paper explains with a qualitative descriptive method with a critical constructivism paradigm through an ethnographic approach to reflect on agrarian reform in the frame of the economic system. The research was conducted in West Java Province until 2022. The research data comes from primary data from interviews and secondary data from processed various literature sources. The data is analyzed to understand how agrarian reform can be achieved and provide reflections to earn an economic system that has implications for Indonesia's development in 2045. The results showed that agricultural reform carried out primarily in West Java Province and in general in Indonesia had an impact on economic growth/increase in the economic system in line with realizing the vision of Golden Indonesia 2045, even though there were obstacles, namely disputes, conflicts and judicial cases as the residual economic value of the land.gb777